Discovering the Comic - McFadden, George, 1916- (Book collections on Project MUSE., 1982)
Arguing that the comic is a quality of literary works of art in other forms as well as comedy, George McFadden finds its essence in the maintenance of some literary feature--a situation, a character--as itself despite threats to alter it. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.